Assessment of the regenerative potential of macro-porous chitosan-calcium simvastatin scaffolds on bone cells - De Oliveira Gallinari, Marjorie; Bordini, Ester Alves Ferreira; De Toledo Stuani, Vitor; Cassiano, Fernanda Balestrero; De Melo, Camila Correa Da Silva Braga; De Almeida, Juliano Milanezi [UNESP]; Cintra, Luciano Tavares Ângelo [UNESP]; De Souza Costa, Carlos Alberto [UNESP]; Soares, Diana Gabriela (FapUNIFESP (SciELO), 2023)
This study evaluated the bioactive potential of a macro-porous chitosan scaffold incorporated with calcium hydroxide (CH-Ca) and functionalized with bioactive doses of simvastatin (SV) for bone tissue regeneration. Initially, the bioactive dose of SV in osteoblastic cells (SAOS-2) was determined. For the direct contact experiment, SAOS-2 cells were plated on scaffolds to assess cell viability and osteogenic differentiation. The second assay was performed at a distance using extracts from scaffolds incubated in culture medium to assess the effect of conditioned medium on viability and osteogenic differentiation. The initial screening showed that 1 μM SV presented the best biostimulating effects, and this dose was selected for incorporation into the CH-Ca and pure chitosan (CH) scaffolds. The cells remained viable throughout the direct contact experiment, with the greatest cell density in the CH-Ca and CH-Ca-SV scaffolds because of their higher porosity. The CH-Ca-SV scaffold showed the most intense bio-stimulating effect in assays in the presence and absence of osteogenic medium, leading to an increased deposition of mineralized matrix. There was an increase in the viability of cells exposed to the extracts for CH-Ca, CH-SV, and CH-Ca-SV during the one-day period. There was an increase in ALP activity in the CH-Ca and CH-Ca-SV; however, the CH-Ca-SV scaffold resulted in an intense increase in the deposition of mineralized nodules, approximately 56.4% at 7 days and 117% at 14 days, compared with CH (control). In conclusion, functionalization of the CH-Ca scaffold with SV promoted an increase in bioactivity, presenting a promising option for bone tissue regeneration
Keywords: Chitosan; Simvastatin; Tissue Engineering